Hypocomplementemic Atypical IgA Vasculitis: A Case Report - Chan, Melvin; Hanna, Melisha Gayle; Willard, Nicholas; Treece, Amy; Dixon, Bradley Patton (Frontiers in Pediatrics, 2022)
IgA vasculitis (IgAV, also known as Henoch-Schönlein purpura or HSP) is a vasculitis of small vessels involving multiple organs, particularly of the joints, gastrointestinal tract, skin, and kidneys. Growing laboratory evidence has shown that complement plays a key role in the pathogenesis of IgAV, although direct evidence of this association in patients is lacking. We report a child with IgAV associated with clinical features of hypertension, nephrotic range proteinuria, acute kidney injury, and low serum C3, with histopathologic findings on renal biopsy of membranoproliferative glomerulonephritis with C3 and IgA co-dominance, and extensive complement derangements. This case report suggests that complement modifies the pathogenesis of IgAV, and further investigation into complement-targeted therapy in cases of refractory IgAV may be beneficial.